MAPPING AND REMOVING QUARRY BLAST EVENTS FROM SEISMICITY CATALOGS - Wiemer S.; Baer M. (My University, 2000)
We present an algorithm to identify and remove quarry explosions from earthquake catalogs while retaining a maximum amount of data. For most seismicity studies, quarry blasts are a data contamination that obscures natural phenomena under investigation. Based on the fact that most quarry blasts are performed during daytime hours, we spatially map out the ratio of daytime to nighttime events, Rq. This type of map clearly identifies regions of high quarry activity. A grid search identifies the highest Rq volume, which is subsequently removed from the data. This process is repeated until no volume with an anomalous ratio of daytime to nighttime events with significance greater than 99% remains. Examples for Switzerland, Alaska, and the western United States demonstrate the capabilities of the algorithm, where the algorithm removes 20%, 6%, and 0.75% of the events, respectively. We suggest that computing maps of Rq should be a routine part of any microseismicity study